DAMPAK PENGHAPUSAN SUBSIDI EKSPOR PERTANIAN OLEH NEGARA MAJU TERHADAP KERAGAMAN PEREKONOMIAN NEGARA BERKEMBANG - Nurjanah, Rahma (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2011)
This report is a result of the first from two parts of our research step planned. This research intends: (1) to analyze the impact of export subsidies elimination on agriculture by developed countries, (2) to analyse the impact of export subsidies elimination on macroeconomic performances in developing countries. General equilibrium Model has been used to answer the research purpose. The General Trade Analysis Project was employed as the main tool of analysis. The results show that impacts of export subsidies elimination by European Union (EU) and United States of America (USA) are varied. The elimination of export sibsidies by developed countries results in an increase in the developing countries export. It is, however, this policy fail to improve the real GDP of Developing Countries. Therefore, there is no reason for developing countries to refuse the agreement to eliminate the export subidies that has been prevailed in the last time. In addition, the developing countries including Indonesia should force developed countries to eliminate all trade protection. Keywords: Export Subsidies, Trade Liberalisation, GTAP Analysis